2003
DOI: 10.1267/ahc.36.393
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Mechanism of Elevator Movement

Abstract: The elevator movement of the matrix cell is synchronous with the mitotic cycle. Its mechanism has been thought to be due to cyclic changes in cell adhesion to the neighboring cells and the basement membrane. The present study aims to analyze the cytoplasmic changes by means of immunohistochemical investigations of the distributions of the adhesion molecules, N-cadherin, a-catenin, bcatenin, F-actin, etc. It was found that the adherent junctions and junctions to ECM of the matrix cell disintegrate during mitosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Our immunohistochemical observations on changes in distribution of adhesion molecules during mitotic cycle unveiled the molecular mechanism of the elevator movement (Fujita and Yasuda, 2003): Adhesion apparatuses of N-cadherin-catenin-actin complexes dissociate during mitosis releasing the intercellular adhesion from the neighboring cells. Simultaneously, the release of adhesion of the integrin systems takes place and the mitotic matrix cells are rounded off and inevitably attracted to the junctional complexes on the ventricular surface (Fig.…”
Section: Molecular Mechanism Of the Elevator Movementmentioning
confidence: 71%
See 1 more Smart Citation
“…Our immunohistochemical observations on changes in distribution of adhesion molecules during mitotic cycle unveiled the molecular mechanism of the elevator movement (Fujita and Yasuda, 2003): Adhesion apparatuses of N-cadherin-catenin-actin complexes dissociate during mitosis releasing the intercellular adhesion from the neighboring cells. Simultaneously, the release of adhesion of the integrin systems takes place and the mitotic matrix cells are rounded off and inevitably attracted to the junctional complexes on the ventricular surface (Fig.…”
Section: Molecular Mechanism Of the Elevator Movementmentioning
confidence: 71%
“…Simultaneously, or sometimes lagging behind time, the release of adhesion of integrin (IGRN) from ECM takes place. Adapted from Fujita and Yasuda, 2003. cell (Fig. 12A).…”
Section: Molecular Mechanism Of the Elevator Movementmentioning
confidence: 99%
“…On the other hand, folliculo-stellate cells which do not produce hormones began expressing only E-cadherin and stopped expressing N-cadherin [ 7 ]. Fujita and Yasuda [ 2 ] reported that, in the matrix cell of the developing central nervous system, the dissociation and reassembly of N-cadherin-catenin complexes which occurs during mitosis causes elevator movement. It is likely that a similar mechanism plays a role during proliferation, differentiation and distribution of hormone-producing cells in the adenohypophysis.…”
Section: Resultsmentioning
confidence: 99%
“…The interkinetic cell shows a polarized bipolar structure, whereas the M-phase cell is round. Fujita and Yasuda [23] have suggested that this morphological difference is due to a change in cell-cell adhesion that is mediated by cadherin-catenin complexes within each cell and by cadherin-cadherin interactions between the two cells. The interkinetic cells adhere to each other via cadherin-catenin complexes, and these complexes are anchored to F-actin (Fig.…”
Section: Cell Cycle-dependent Ca 2+ Mobilization and Cell-cell Adhesimentioning
confidence: 99%
“…3A). During M-phase, the cadherin-catenin complex dissociates, thereby disrupting cell-cell adhesion [23]. As a result, M-phase cells are round (Fig.…”
Section: Cell Cycle-dependent Ca 2+ Mobilization and Cell-cell Adhesimentioning
confidence: 99%